If I could turn back time [compact disc] : Cher's greatest hits - Cher, 1946- (Geffen Records, 1999)
"There are not too many other performing artists that can boast the thriving diversity that Cher can. During her show business career, currently over 30 years, the mere mention of her name invokes controversy, curiosity, but mostly incredible success. Not only has Cher had an extraordinary recording career, but she also is a television superstar (with Sonny Bono and solo) and an accomplished, Academy-Award-winning actress."--Container insert.